The Importance of Sport for Members of the Community of Deaf - Šešum, Mia; Isaković, Ljubica; Radić šestić, Marina; Kovačević, Tamara (Specijalna edukacija i rehabilitacija, 2023)
The Importance of Sport for Members of the Deaf Community Introduction. Apart from developing physical skills, a characteristic of sport is that it also helps the socialization of the persons who do it. Thus, it is a rather significant system of activities in the lives of people who are deaf or hard of hearing. Considering the fact that these persons are often marginalized by the typical population, participating in sports activities may contribute to their visibility to a great extent and thus to their inclusion in the social community. It is important to underline that an individual’s deafness or being hard of hearing does not represent a limiting factor for their doing sports if the function of the center of gravity is preserved. Objective. The aim of this work was to provide a systematic insight into the possibilities of the deaf to participate in sports activities through the analysis of the available literature, as well as to indicate the importance that sports can have in their lives. Methods. The descriptive method, analysis, synthesis, and content evaluation were used. Results. Sports are an important component in the lives of many deaf and hard-of-hearing people. Deaf and hard-of-hearing persons may do sports as part of organized activities, independently, for recreational purposes, but also professionally. Professional deaf and hard-of-hearing athletes have the possibility of taking part in specialized competitions which are intended for persons with disabilities or only for deaf and hard-of-hearing persons, as well as in competitions in which predominantly typical athletes participate. Conclusion. In order to achieve the inclusion of the deaf, it is important to use the potential of sports activities as equally accessible to deaf people and members of the typical population.